Maxillary nerve block via the greater palatine canal: An old technique revisited - Aoun, Georges (J Int Soc Prev Community Dent, 2015)
BACKGROUND: Maxillary nerve block through the greater palatine canal is rarely adopted by dental practitioners due to lack of experience in the technique at hand which may lead into several complications. Nevertheless, it is an excellent method to achieve profound anesthesia in the maxilla. This review focuses on the anatomy as well as the indications, contraindications, and complications associated with this technique. MATERIALS AND METHODS: A literature search was performed using the scientific databases (PubMed and Google Scholar) for articles published up to December 2014 in English, using the key words “maxillary nerve block via the greater palatine canal.” A total of 34 references met the inclusion criteria for this review and were selected. CONCLUSION: Block of the maxillary nerve through the greater palatine canal is a useful technique providing profound anesthesia in the hemi-maxilla, if practiced properly.